Popular choice and managed democracy : the Russian elections of 1999 and 2000 - Colton, Timothy J., 1947- (Brookings Institution Press, 2003)
Twice in the winter of 1999-2000, citizens of the Russian Federation flocked to their neighbourhood voting stations and scratched their ballots in an atmosphere of uncertainty, rancor and fear. This book is a tale of these two elections - one for the 450-seat Duma, the other for president.